Pengarusutamaan Gender Dalam Pengembangan Sistem Pendayagunaan Zakat Melalui Modal Usaha Bergulir Di Desa Sindanglaka Kabupaten Cianjur - Solihah, Cucu; Mulyadi, Muhammad Budi; Mulyana, Aji (Jurnal Hukum & Pembangunan, 2019)
The participation of women in the community welfare improvement program is a choice that must be developed today. The gender mainstream is the right policy considering the women is vunerable to poverty crises. The business development patterns by implementing the revolving capital coming from zakat community development of BAZNAS is an alternative effort to improve the welfare of women. It is assessed from the women's ability in maintaining business and the managing capital in implementing the programs whose capital is collected from zakat